PROGRAM KELUARGA HARAPAN (PKH) DALAM MENGENTASKAN KEMISKINAN DI KELURAHAN TELUK BINJAI KECAMATAN DUMAI TIMUR KOTA DUMAI - Salam, M. Fathan; Widodo, Teguh (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study evaluates the effectiveness of the Family Hope Program (PKH) in alleviating poverty in the Teluk Binjai sub-district of Dumai. Involving 79 PKH participants and utilizing a quantitative approach with simple random sampling, the data analysis indicates that the training within PKH significantly influences poverty alleviation, with a significance value of 0.000 (α < 0.05) in the t-statistic test. The simultaneous F-test confirms that PKH significantly contributes to poverty alleviation, with a significance value of 0.000. These results suggest that PKH is effective in reducing poverty levels in the area. Therefore, the program has a significant positive impact, reflecting the success of the Indonesian government's efforts to address various dimensions of poverty through initiatives such as PKH at the local level. Keywords: PKH, Poverty, Effectiveness, Society